MILITARY NARRATIONS IN THE UKRAINIAN POPULAR NOVEL - Poliszczuk, Jarosław (Porównania, 2014)
The concept of war and struggle, similarly as the reflection of defeat and resignation from the recent past became the main topic of the novels of Ukrainian writers, e.g. Oksana Zabužko, Vasyl Šklar, Lina Kostenko, Sergiy Žadan, etc. The researching of the military rhetoric in the article is based on the famous contemporary books The Notes of Ukrainian Crazy Man by Lina Kostenko and The War and We by Sergiy Pantiuk. The analysis of the novels gives us the possibility to find out and to understand the place of war in the post-colonial culture and in the space of globalization. The interesting fact is that, in their novels, both authors made some prognoses for the future, in particular regarding the contemporary local war in Ukraine.